1997
DOI: 10.1002/(sici)1096-9861(19970407)380:2<175::aid-cne3>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

A population of nicotinic receptors is associated with thalamocortical afferents in the adult rat: Laminal and areal analysis

Abstract: In the adult rat brain, a prominent population of nicotinic cholinoceptors binds 3H-nicotine with nanomolar affinity. These receptors are abundant in most thalamic nuclei and in neocortical layers 3/4, which receive a major thalamic input. To test whether cortical nicotinic receptors are associated with thalamocortical afferents, unilateral excitotoxic (N-methyl-D-aspartate) lesions were made in one of four thalamic nuclear groups (anterior, ventral, medial geniculate, or dorsal lateral geniculate) or in tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 72 publications
4
40
0
Order By: Relevance
“…Thalamocortical projections are known to contain nicotinic receptors (Gil et al, 1997), and thalamic lesions have been shown to markedly reduce nicotine binding in the midlayers of cortex (Prusky et al, 1987;Sahin et al, 1992;Lavine et al, 1997;Gioanni et al, 1999). In order to test the hypothesis that nicotine triggers action potentials preferentially in thalamocortical terminals of the prefrontal cortex, we made unilateral radiofrequency lesions in the anterior thalamus in five animals and performed sham lesions in three animals.…”
Section: Effects Of Thalamic Lesionssupporting
confidence: 90%
See 3 more Smart Citations
“…Thalamocortical projections are known to contain nicotinic receptors (Gil et al, 1997), and thalamic lesions have been shown to markedly reduce nicotine binding in the midlayers of cortex (Prusky et al, 1987;Sahin et al, 1992;Lavine et al, 1997;Gioanni et al, 1999). In order to test the hypothesis that nicotine triggers action potentials preferentially in thalamocortical terminals of the prefrontal cortex, we made unilateral radiofrequency lesions in the anterior thalamus in five animals and performed sham lesions in three animals.…”
Section: Effects Of Thalamic Lesionssupporting
confidence: 90%
“…The significance of any treatment on sEPSC frequency was assessed with Kolmogorov-Smirnov analysis for each neuron (data from the peak 20 s compared to 20 s of baseline); Po0.01 was considered significant. Where described in text and figures, Student's t-tests were used to compare responses from several neurons (Prusky et al, 1987;Sahin et al, 1992;Lavine et al, 1997;Gioanni et al, 1999). Baseline levels of sEPSCs were similar in mean and range across groups of neurons, and analysis by one-way ANOVA across experimental groups revealed no significant effect of group (rats, lesioned rats, wild-type or knockout mice) on baseline sEPSCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nicotinic receptors have been identified on the thalamocortical cells that receive the cholinergic input from the tegmentum. It was shown in the rat that these receptors probably result from the assembly of the a4 and p2 subunits (63). In the cat, the activation of the cholinergic input of the thalamus was shown to disrupt spindle activity by an initial fast membrane depolarization of thalamocortical neurons, mediated by nicotinic receptors, followed by a prolonged depolarization mediated by muscarinic receptors (62).…”
Section: Discussionmentioning
confidence: 97%